Acute mastoid abscess secondary to partially treated upper respiratory tract infection: a case report - Halimuddin S,; Asma A, (Penerbit UKM, 2010)
Acute mastoid abscess is common in daily practice. In children, it is usually caused by unsuccessful treatment or partially treated acute otitis media (AOM). Some authors had reported that chronic suppurative otitis media (CSOM) can be the source of infection but it is usually associated with the presence of cholesteatoma. A case of an acute mastoid abscess in a 7 year old girl is presented. She had a history of severe otalgia with left post auricular swelling for 3 days. Clinically she was febrile, the left otoscopy showed diffuse post auricular swelling and sagging of the posterior wall of the external canal. She underwent an emergency cortical mastoidectomy for the left mastoid abscess and had an uneventful recovery. In conclusion, this patient was partially treated with antibiotics which increased the risk for ‘masked mastoiditis’, and she later developed a mastoid abscess. Therefore we advocate that all AOM patients should be treated with antibiotics at least for a duration of one week.